Retention Bans Are Beneficial but Insufficient to Stop Shark Overfishing - Leonardo Manir Feitosa; Alicia M. Caughman; Nidhi G. D'Costa; Sara Orofino; Echelle S. Burns; Laurenne Schiller; Boris Worm; Darcy Bradley (Fish and Fisheries, 2025)
Sharks are among the most threatened groups of exploited fishes, comprising common bycatch across many fisheries. Management efforts intended to safeguard threatened species have increasingly focused on retention bans to reduce bycatch mortality. However, the population effects of such measures remain unevaluated across species. We combined available data from 160 studies providing estimates of at‐vessel or post‐release mortality for 147 taxa caught by different fishing gears to create random‐forest regression models and predict mortality rates for 341 shark species incidentally captured by longlines or gillnets. Smaller‐bodied species inhabiting shallow waters were more likely to suffer at‐vessel mortality compared to their deep‐water counterparts, for which post‐release mortality was more likely to occur. We then used results for longlines to simulate the effect of retention bans in reducing fishing mortality to sustainable levels. Our metric consists of the ratio between the proportion of each species' population caught and discarded ( P MAX ) under a retention ban divided by the fishing mortality ( F ) predicted to achieve maximum sustainable yield ( F MSY ). Our calculations show that a retention ban yielded an average ~ three‐fold higher P MAX compared to F MSY , with 18% of the species having P MAX /F MSY P MAX /F MSY P MAX /F MSY > 5. For threatened species, median P MAX /F MSY = 2.28 and non‐threatened ones had median P MAX /F MSY = 2.77. Our study shows that retention bans could reduce shark mortality, but must be combined with additional measures to stop overfishing, especially for low‐productivity species.